Relationship between technical-tactical indicators of attention and creativity and effort zones in youth football players during competitions - Oprea, B.; Potop, V.; Mihailescu, L. E.; Fleancu, J. L.; Cojanu, F.; Cucui, G. G.; Pricop, A. D. (Pedagogy of Physical Culture and Sports, 2025)
Background and study aim: Cognitive performance, specifically attention and creativity, contributes to the tactical effectiveness of youth football players. This contribution becomes evident when actions are executed under competitive physiological constraints. Examining how physical demands interact with perceptual and cognitive processes may support the development of training methodologies and competitive decision-making strategies. This study aims to analyze the relationship between technical-tactical indicators of attention and creativity and effort-zone parameters in young football players.